The Relationship between Self-Awareness and Humility in Generation Z in Kayuroya Village, Minahasa Regency - Jacobis, Kerin I.; Solang, Deetje J.; Hartati, Meike E. (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Generation Z is a generation that has grown up in an era of rapid modern technology. This has triggered changes in the way Generation Z thinks and acts, including in terms of values and character. Self-awareness and humility are two characters that are considered important to build in shaping a good personality in generation Z. This study aims to determine the relationship between self-awareness and humility in generation Z in Kayuroya village, Minahasa Regency. This study used a quantitative approach. The population amounted to 90 people by looking at the Isaac and Michael sample size determination table for an error rate of 10%, the sample amounted to 68 people. Self-awareness was measured using an awareness scale based on Brown and Ryan's (2003) theory or The Mindful Attention Awareness Scale (MAAS). Humility was measured using the humility scale from Jeffrey Charles Elliott (2010). Based on the research conducted, it is concluded that there is no relationship between self-awareness and humility in generation Z in Kayuroya village, Minahasa Regency where the empirical correlation coefficient (rxy) value is 0.397 ≥ 0.05 and the rcount value is -0.032 0.239. The percentage of self-awareness and humility in generation Z in Kayuroya village, Minahasa Regency is at a low level, where there are 42 respondents (61.8%) low self-awareness and 26 people (38.2%) high self-awareness, and 37 respondents (54.4%) low humility and 31 people (48.6%) have high humility